Sliding of coherent twin boundaries - Zhang-Jie Wang; Qing-Jie Li; Yao Li; Long-Chao Huang; Lei Lu; Ming Dao; Ju Li; Evan Ma; Subra Suresh; Zhi-Wei Shan (Nature Communications, 2017)
Coherent twin boundaries (CTBs) in face-centered cubic metals are usually considered unable to slide at room temperature. Here, the authors use in situ transmission electron microscopy and molecular dynamics to show CTB sliding in copper nanopillars when leading and trailing partial dislocations have similar Schmid factors.